Composition, Density Species and Coverage of Seagrass in Nara Bay Beach, North Lombok - Katarina Hesty Rombe; Khairul Jamil; Agus Surachmat; Dwi Rosalina; Abdul Rahman; Kelfindo Efraim (Berkala Perikanan Terubuk, 2023)
Nara Bay Beach has enormous marine resource potential with high biodiversity. One of the marine resources owned by Nara Bay Beach is seagrass beds. The purpose of this study was to calculate the composition, species density and cover of seagrass and to measure water quality parameters at Nara Bay Beach. The method used in collecting seagrass data at the location is the quadrant transect. The number of stations used is 3 stations. The results showed that Cymodocea rotundata had the highest species composition value of 73.48% (ST.3), the highest density was obtained by Syringodium isoetifolium of 161.8 (ST.3), the highest seagrass cover was obtained at ST. 3 and for water quality parameters (temperature, salinity, currents and pH) are still within optimum limits for seagrass growing.